THEORETICAL BASICS OF USING MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The use of ICT in the professional activities of teachers is one of the main directions of modernization of the education system of the country. The article discusses information and communication skills and the mechanisms and methods of developing this skill in teachers of the humanities.